"He helped me to free myself from provincial culture". Romano Bilenchi’s Unpublished Letters to Carlo Bo (1937-1972) (Prassi Ecdotiche della Modernità Letteraria, 2021)
The essay examines Romano Bilenchi’s unpublished letters to Carlo Bo held at the Archivio Urbinate of the Fondazione Carlo and Marise Bo. The correspondence offers a wealth of information on the relationship between Bilenchi and the eminent critic and translator. It specifically sheds new light on their journalistic collaboration and discussion of each other’s works from the late Thirties to the Seventies. A noteworthy selection of twenty letters is edited in the second part of the article with a commentary elucidating references to the coeval literary society and the foreign works read by Bilenchi following Bo’s advice.
Keywords: Romano Bilenchi; Carlo Bo; Unpublished Letters; Literary Criticism; Journalism; Translation; French Literature; Spanish Literature; Italian Literature